Black carbon-doped TiO2 films: Synthesis, characterization and photocatalysis - Varnagiris, Sarunas; Medvids, Arturs; Lelis, Martynas; Milcius, Darius; Antuzevics, Andris (Elsevier B.V., 2019)
Black colour TiO2 films were synthesized on amorphous fused silica substrates by DC magnetron sputtering technique with carbon powders placed at the working magnetron surface. Comprehensive sample analysis by X-ray diffraction, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy showed that the rutile/anatase heterostructure TiO2 films were successfully formed. Moreover, observation of Osingle bondTisingle bondC bonds confirmed that TiO2 phase was doped by carbon additives. Scanning electron microscopy, atomic force microscopy and X-ray diffraction were used to identify the effect of deposition time and TiO2 film thickness on the surface morphology, roughness and crystallite size. Results of electron spin resonance showed that oxygen vacancies were generated on the surface with trapped unpaired electrons. Optical analysis by UV–vis light spectrophotometer showed that TiO2 films with carbon additives improve its capability to absorb visible light. Accordingly, methylene blue bleaching experiments under UVsingle bondA and visible light irradiation showed that black colour TiO2 films are capable to decompose methylene blue solution at both UVsingle bondA and visible light irradiation. ----/ / / ---- This is the preprint version of the following article: S. Varnagirisa, A. Medvids, M. Lelisa, D. Milciusa, A. Antuzevics, Black carbon-doped TiO2 films: Synthesis, characterization and photocatalysis, Journal of Photochemistry and Photobiology A: Chemistry 382, 111941 (2019), which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S1010603019303442. This article may be used for non-commercial purposes in accordance with Elsevier Terms and Conditions for Sharing and Self-Archiving. This work is licensed under a CC BY-NC-ND 4.0 license.
© 2019. This work is licensed under a CC BY-NC-ND 4.0 license.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Photocatalysis; Black TiO2; Carbon-doped TiO2; Magnetron sputtering; Band gap; Visible light